Goigs chanté "la Vierge de la Salud de Pia" (air moderne) (French) - xw42n835f; zk51vh138 (k930bx43m; 9306sz60j, 1963)
Description analytique : Goigs chanté "la Vierge de la Salud de Pia" (air moderne) (French)